2006
DOI: 10.1152/japplphysiol.01307.2005
|View full text |Cite
|
Sign up to set email alerts
|

Single-breath test in lateral decubitus reflects function of single lungs grafted for emphysema

Abstract: The slope of alveolar plateau for nitrogen derived from the single-breath test is useful to assess the function of bilateral lung grafts, but this technique is not applicable to patients with single-lung grafts due to the confounding influence of the native lung. We tested the hypothesis that the nitrogen slope measured in lateral decubitus with the graft in nondependent position may primarily reflect the distribution of ventilation in this lung. Fifteen patients with single-lung transplantation for emphysema,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…For instance, the weight of the lung is known to produce a positive N 2 phase-III slope due to the greater specific ventilation of the dependent versus the nondependent lung zones and the preferential emptying of the basal lung zones at the beginning of expiration. Hence, depending on whether lung diseases preferentially affect the basal or apical lung zones, the N 2 phase III slope may be affected differently, and one study has elegantly shown how gravity can even be exploited to reveal peripheral lung disease in a part of the lung that is brought into a preferential position along the line of gravity [87]. The vital capacity SBW maneuver is also regularly used to simply determine the closing volume (or closing capacity) as a measure of small airways closure, which can also have a preferential topographical distribution.…”
Section: Washout Testsmentioning
confidence: 99%
“…For instance, the weight of the lung is known to produce a positive N 2 phase-III slope due to the greater specific ventilation of the dependent versus the nondependent lung zones and the preferential emptying of the basal lung zones at the beginning of expiration. Hence, depending on whether lung diseases preferentially affect the basal or apical lung zones, the N 2 phase III slope may be affected differently, and one study has elegantly shown how gravity can even be exploited to reveal peripheral lung disease in a part of the lung that is brought into a preferential position along the line of gravity [87]. The vital capacity SBW maneuver is also regularly used to simply determine the closing volume (or closing capacity) as a measure of small airways closure, which can also have a preferential topographical distribution.…”
Section: Washout Testsmentioning
confidence: 99%
“…Timedependent within-breath imaging of ventilation heterogeneity would allow a more rigorous comparison of imaging data with gas mixing indices such as a phase III slope, which depends on both specific ventilation heterogeneity and flow asynchrony. Recently, an elegant example in unilateral lung transplant patients has exploited quasi-static lung volume-dependent CT imaging to demonstrate how flow asynchrony between the native and the transplanted lung translates into different parts of the phase III slope collected at the patient's mouth (141). Applying a similar approach at smaller scales of unit lung volume could enable the quantification of intra-regional ventilation heterogeneity, which is thought to be present in normal human subjects based on indirect measurement.…”
Section: Model Simulations Of Gas Mixing: Specific Ventilation and Flmentioning
confidence: 99%
“…Data obtained in the transplant recipients were compared with data obtained in 10 normal subjects and 12 nontransplanted patients with a variety of ILD. The group of healthy controls was the same as that used in our laboratory's previous study (11) and was matched for age and sex with the donors. At the time of studies, all transplant recipients were clinically stable and free of acute infection and rejection.…”
Section: Methodsmentioning
confidence: 99%
“…However, our laboratory recently showed in patients with single-lung transplantation for emphysema that this limitation can be overcome by performing the test in lateral decubitus (11). When the patient was in lateral decubitus with the graft in the nondependent position, this lung contributed all of the volume expired in the last part of the washout.…”
mentioning
confidence: 99%